2006
DOI: 10.1021/jp060624c
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties and Defect Chemistry of TiO2 Single Crystal. IV. Prolonged Oxidation Kinetics and Chemical Diffusion

Abstract: Measurements of both electrical conductivity and thermoelectric power were used to monitor the equilibration kinetics of undoped single-crystal TiO(2) during prolonged oxidation at 1123 and 1323 K and p(O(2)) = 75 kPa. Two kinetics regimes were revealed: kinetics regime I (rapid kinetics), which is rate-controlled by the transport of oxygen vacancies, and kinetics regime II (slow kinetics), which is rate-controlled by the transport of titanium vacancies. The incorporation of titanium vacancies allows undoped p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
185
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(186 citation statements)
references
References 14 publications
1
185
0
Order By: Relevance
“…Studies of the electrical properties and defect chemistry continue to appear for this material in both single crystal [219][220][221][222] and nanostructured form [223]. Yet this material to date has not yielded systems for evolving H 2 and O 2 at the 10% benchmark efficiency level.…”
Section: Recent Work On Tio 2 On Photosplitting Of Water Ormentioning
confidence: 99%
“…Studies of the electrical properties and defect chemistry continue to appear for this material in both single crystal [219][220][221][222] and nanostructured form [223]. Yet this material to date has not yielded systems for evolving H 2 and O 2 at the 10% benchmark efficiency level.…”
Section: Recent Work On Tio 2 On Photosplitting Of Water Ormentioning
confidence: 99%
“…Then TiO 2 may be better represented by the formula TiO 2+x or, more precisely Ti 1-x O 2-y , where ( 2). x y > / It was shown that the properties of the p-type TiO 2 are determined by titanium vacancies, which are formed during the prolonged oxidation [28].…”
Section: Incorporation Of Aliovalent Ions (Cations or Anions)mentioning
confidence: 99%
“…It has been shown that while the equilibria (1)-(3) may be established relatively fast, the formation of titanium vacancies, represented by equilibrium (4), is extremely slow [28]. Therefore, the required concentration of defects may be manipulated not only by oxygen activity during processing, but also by the kinetic factor (equilibration time).…”
Section: Incorporation Of Aliovalent Ions (Cations or Anions)mentioning
confidence: 99%
See 2 more Smart Citations